Model Perilaku Berbagi Pengetahuan antar IKM dalam Sebuah Sentra - Cindy Marika Amalia Wibowo; Ceicalia Tesavrita (Jurnal Rekayasa Sistem Industri, 2017)
This research aims to map SME’s behaviour in knowledge sharing in a SME’s center. Knowledge sharing activity is one of key factor in knowledge management, where individual/group knowledge can be disseminated well and increase organization intellectual capital. Many research has identified variables that are affecting knowledge sharing activity, but the results cannot be generalized. This research uses literature study and interview to identify those variables in two SME’s center in Java. The questionnaires then developed based on the 35 variables that are identified.  Factor analysis is used to analyze the data and generate six factors that are affecting knowledge sharing activity in SME’s center, such as job characteristic, technology, internal individual, environmental influence, reward system, and job security. The result of SEM show that technology, internal individual, and environmental influence has positive relationships toward knowledge sharing activity, while job characteristic and reward system has negative relationships toward knowledge sharing activity.